Pencitraan pada pankreolithiasis dengan pankreatitis kronis: laporan kasus - Indira Prawita Martini; Nyoman Srie Laksminingsih; Elysanti Dwi Martadiani (DiscoverSys Inc., 2020)
Background: Pancreolithiasis or pancreatic calculus is a rare case. Men suffer more than women with a ratio of 2-3:1 and have an incidence of 1-8:100.000. Pancretolithiasis itself is a sequela of chronic pancreatitis. Accompanied by non-specific complaints, epigastric abdominal pain that radiates to the back to the left shoulder and nausea, vomiting which causes weight loss and malnutrition. Radiological examination can help the clinician in. establish a diagnosis where the laboratory results are also not specific enough to diagnose chronic pancreatitis. The aim of this report is to determine the radiological features of pancreolithiasis accompanied by chronic pancreatitis.Case: A 54-year-old woman with complaints of pain in the epigastric region for approximately 3 months, accompanied by nausea and vomiting, especially after eating which resulted in weight loss of approximately 10 kilograms. In laboratory tests, an increase in total cholesterol, LDH and hyperkalemia was found. There is no increase in amylase and lipase and hepatic function. On plain abdominal radiograph, ultrasound and CT scan, it is found that there is a stone image accompanied by imaging of chronic pancreatitis.Conclusion: Pancreatic calculus is a rare condition. More common in male gender, patients with pancreolithiasis have non-specific discharge. Alcohol use is said to be the biggest factor in pancreolithiasis. On plain abdominal radiograph, ultrasound and CT scan can reveal the presence of stones in the pancreas and the presence or absence of involvement of the pancreatic parenchyma.